Inflammatory imbalance and activation deficits in T cells of myasthenia gravis patients revealed by proteomic profiling - Bhandage, Amol K.; Punga, Anna Rostedt (Frontiers in Immunology, 2025)
Myasthenia gravis (MG) is a heterogeneous autoimmune disorder characterized by neuromuscular transmission failure and skeletal muscle fatigability, with a pathophysiology involving both cellular and humoral immune components. Despite growing interest in the immunological etiology of MG, few functional studies have addressed the role of T cells, and most existing work has focused on quantifying immune cell subsets using flow cytometry. In this study, a comparative in vitro analysis of resting and activated CD4+ and CD8+ T cells from MG patients and healthy controls (HC) was performed using the multiplex Proximity Extension Assay (PEA) proteomics to assess the secretion of inflammatory proteins, including cytokines and chemokines, and to define the inflammatory status of T cells in MG. Data analysis was performed using the Boruta algorithm to detect both linear and non-linear patterns, followed by multiple testing corrections, and correlation analyses. The results revealed distinct alterations in the secretion profiles of several inflammatory proteins in MG compared to HC across both T cell subsets, regardless of activation state. Notably, resting CD4+ T cells from MG patients secreted higher levels of VEGFA, TNFRSF9, TWEAK, CCL20, HGF, CCL19, TRAIL, IL18, and TNF-β whereas resting CD8+ T cells secreted higher levels of IL-12B, TRAIL, CCL23, CD244, CXCL11, CCL20, VEGFA, PD-L1, and OSM relative to HC. In contrast, activated CD4+ and CD8+ cells from MG patients exhibited a blunted secretion profile compared to HC, suggesting functional exhaustion. Furthermore, MG-ADL scores correlated with the secretion levels of 14 proteins from resting CD4+ cells, including seven cytokines, five chemokines, and two matrix metalloproteins. Some of the CD4+ T cell secreted proteins also correlated with their corresponding serum or plasma levels in vivo. Overall, these findings indicate that T cells in MG exhibit a skewed inflammatory profile characterized by heightened basal activation and impaired inducibility, suggestive of an exhausted phenotype. The interplay between these altered T cell functions and aberrant B cell responses in MG warrants further investigation and may provide novel insights into disease immunopathophysiology as well as opportunities for targeted immunomodulatory therapies.